Aplikasi perhitungan tingkat kesuburan perairan dengan Metode Carlson pada perairan urban Danau Polder Air Hitam di Kota Samarinda: Application of Carlson trophic state index on trophic state determination of urban Polder Air Hitam Lake in Samarinda City - Hamdhani, Hamdhani; Sharaha , Musyiir; Fadhilla , Febby Nur; Harijono , Gregorius Viky (Faculty of Fisheries and Marine Science, Mulawarman University, 2023)
In general, various human activities cause eutrophication in water bodies. Lentic system is vulnerable to discharge of pollutants from surrounding areas. Similar scenarios most likely occur in Polder Air Hitam Lake in Samarinda City. The goal of this study was to investigate the trophic status of this urban lake using modified Carlson index with the indicator of chlorophyll-a and total phosphate/ Spatially the variation of chlorophyll-a was 32.6 – 97.3 µg/L, and total phosphate was 0,141 – 0,225 mg/L. The calculation of Carlson trophic state index resulted 73.78, which indicated hypereutrophic status. This condition was not ideal for a healthy lentic system. In the future a related treatment is required to optimize multiple functions of this urban lake.